PERANAN PENGELOLA REKOD DAN ARSIP ORGANISASI PADA LAYANAN INFORMASI PUBLIK : KEWAJIBAN ORGANISASI PUBLIK MENGHADIRKAN PPID - Safitri, Dyah (UI Scholars Hub, 2019)
This research is intended to understand the description of the application of the Public Information Disclosure Law related to the management of records and archives. Records and archive managers play a role in determining which access to information can be given to the public based on applicable laws and regulations. The approach taken is through literature review on public information disclosure that is closely related to the management of records and archives in countries that have used the Public Information Disclosure Act. Indonesia already has a legal umbrella for both the Public Information Disclosure Act and the Archive Law which should have a strong foundation in the application of information access to the public. The implementation must obtain knowledge about access to public information. This research is only limited to seeing the presentation of ministry PPIDs in providing access to public information that has been selected by the role of record managers and archives. Theoretically provides insight into the theory of public information openness associated with the management of records and archives. Practically, if the management of records and archives can be done well in public bodies the issue of public information disclosure can be resolved properly.